Recent syncope and unexplained falls are associated with poor cognitive performance - Kenny, Rose; Boyle, Gerard (My University, 2015)
Objective: to compare cognitive performance in participants with and without syncope and unexplained falls in a large population representative sample aged 50 years or older. Methods: participants of the Irish longitudinal study on ageing (TILDA) were studied. Participants with a history of syncope and/or unexplained falls in the past 12 months were compared with those with no reported events. Cognitive performance was measured using the Montreal cognitive assessment (MoCA) score. Multivariate linear regression analysis controlling for potential confounders was performed to compare cognitive function by syncope and falls status. Results: five thousand eight hundred and forty-six participants were analysed, median age 62 years (inter-quartile range = 14), and 54% were female. Five hundred and forty-nine (9.4%) had a syncopal event and/or an unexplained fall in past 12 months. One hundred and two (1.8%) subjects had two-plus syncopal events in the same period. There was a significant association between syncope/falls history and lower MoCA score, following adjustment for all confounders (B = −0.4; −0.69, −0.11; P = 0.006). Higher syncope burden was also associated with lower performance; however, this was largely explained by confounders. There was no age interaction with these findings. Conclusion: participants who experienced syncope and/or non-accidental falls in the previous year have poor global cognitive performance compared with case–controls. There was no effect of age on our results. Further investigation of the association between syncope burden, unexplained falls and cognitive decline is required to establish a relationship between these disorders.
PUBLISHED
Keywords: syncope neurocardiovascular instability cognition epidemiology older people; syncope neurocardiovascular instability cognition epidemiology older people; Ageing